2021
DOI: 10.5985/emcr.20210009
|View full text |Cite
|
Sign up to set email alerts
|

Plastic additives and legacy persistent organic pollutants in the preen gland oil of seabirds sampled across the globe

Abstract: Plastic pollution, and its associated impacts on marine fauna due to chemical contamination, is an area of growing global concern. We analyzed 145 preen gland oil samples from 32 seabird species belonging to 8 families with different foraging habits and life history strategies from around the world for plastic additives and legacy persistent organic pollutants. The additives included two brominated flame retardants (decabromodiphenyl ether, BDE209; decabromo diphenyl ethane, DBDPE) and six benzotriazole UV sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Organophosphate flame retardants have also been detected in fin whales from the North Atlantic (Garcia-Garin et al 2020). A recent study also reported a correlation between plastic additives in the preen oil of several seabird species from different ocean basins and the amount of ingested plastics, while POPs were ubiquitously present (Yamashita et al 2021).…”
Section: Global State Of Knowledge On Mammal and Bird Interactions Wi...mentioning
confidence: 87%
See 1 more Smart Citation
“…Organophosphate flame retardants have also been detected in fin whales from the North Atlantic (Garcia-Garin et al 2020). A recent study also reported a correlation between plastic additives in the preen oil of several seabird species from different ocean basins and the amount of ingested plastics, while POPs were ubiquitously present (Yamashita et al 2021).…”
Section: Global State Of Knowledge On Mammal and Bird Interactions Wi...mentioning
confidence: 87%
“…Plastic additives have also been detected in Arctic-breeding seabird preen oil. While Provencher et al (2020) did not detect phthalates in northern fulmar preen oil from the Canadian Arctic, a recent study showed several other plastic additives in preen oil from seabirds in Alaska and Greenland (Yamashita et al 2021).…”
Section: Monitoring Of Plastic Additives In Mammals and Birds In The ...mentioning
confidence: 88%
“…Here, we modeled the travel distance and travel time of plastic debris stranding on the beaches of Marion Island and Gough Island, two remote islands located in the Sub--Antarctic Indian Ocean and Southern Atlantic Ocean, respectively, where high concentrations of chemical additives have been detected in the preen gland oil of birds. 22 Details on the applied ocean circulation model, the two scenarios investigated and the results are provided in the Appendix. In brief, the model shows that plastic debris from river sources is very unlikely to reach Marion Island.…”
Section: ) Fishing Net Debris Does Not Necessarily Have To Be From a Local Sourcementioning
confidence: 99%
“…The masks were extracted with n-hexane according to Sakuragi et al (2021) . The extracts were acetylated and purified by silica gel column chromatography and benzotriazole-type UV stabilizers were analyzed by gas chromatography–mass spectrometry according to Yamashita et al (2021) . Reproducibility and recovery were confirmed in advance through four replicate analyses of hexane-extracts of a polyurethane bottle with and without spiking of native benzotriazole-type UV stabilizers standards.…”
mentioning
confidence: 99%